Antioxidant Potential and Inhibition of Mitochondrial Permeability Transition Pore by Myricetin Reduces Aluminium Phosphide-Induced Cytotoxicity and Mitochondrial Impairments - Salimi, Ahmad; Jamali, Zhaleh; Shabani, Mohammad (Frontiers in Pharmacology, 2021)
Oxidative stress and mitochondrial dysfunction are involved in mechanisms of cardiac toxicity induced by aluminum phosphide (AlP). AlP-induced cardiotoxicity leads to cardiomyocyte death, cardiomyopathy, cardiac dysfunction, and eventually to severe heart failure and death. Importantly, protecting cardiomyocytes from the death resulting from AlP is vital for improving survival. It has been reported that flavonoids such as myricetin (Myr) act as modifiers of mitochondrial function and prevent mitochondrial damage resulting from many insults and subsequent cell dysfunction. In this study, the ameliorative effect of Myr, as an important antioxidant and mitochondrial protective agent, was investigated in rat heart isolated cardiomyocytes and mitochondria against AlP-induced toxicity, oxidative stress and mitochondrial dysfunction. Treatment of AlP (20 µg/ml) significantly increased cytotoxicity, reduced glutathione (GSH) depletion, cellular reactive oxygen species (ROS) formation, malondialdehyde (MDA) level, ATP depletion, caspase 3 activation, mitochondria membrane potential (ΔΨm) collapse, lysosomal dysfunction and decreased the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) in intact cardiomyocytes. Also, treatment of AlP (20 µg/ml) significantly increased mitochondrial dysfunction and swelling in isolated mitochondria. Myr (80 µM) appeared to ameliorate against AlP-induced cytotoxicity in isolated cardiomyocytes, and significantly lessened the AlP-stimulated intracellular ROS and MDA production, depletion of GSH and increased the activities of SOD, CAT and GSH-Px. Furthermore, Myr (40 and 80 µM) lowered AlP-induced lysosomal/mitochondrial dysfunction, ATP depletion and caspase 3 activation. In the light of these findings, we concluded that Myr through antioxidant potential and inhibition of mitochondria permeability transition (MPT) pore exerted ameliorative role in AlP-induced toxicity in isolated cardiomyocytes and mitochondria, and it would be valuable to examine in vivo effects.